MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN SEJARAH MENGGUNAKAN MODEL PEMBELAJARAN TWO STAY TWO STRAY DENGAN AKTIVITAS WINDOW SHOPPING PADA PESERTA DIDIK XI MIPA 2 DI SMA NEGERI 10 MALANG - ENDANG SETYONINGSIH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to increase the potential for critical thinking in learning history by using the Two Stay Two Tray learning model with Windaw Shopping activities for XI MIPA 2 students at SMA Negeri 10 Malang. This research is a Classroom Action Research (CAR) which is carried out in two cycles, each cycle is carried out in 5 stages, namely planning, implementing, observing, evaluating and reflecting. Class XI MIPA2 SMA Negeri 10 Malang Even Semester 2018/2019 academic year totaled 36 students. The results showed that in the first cycle there were only 15 students who had the ability to formulate problems (41.66%), the ability to find information from various sources was achieved by 15 students (41.66%), 18 students had the ability to record the results of the discussion. (50%), while the ability to communicate was achieved by 16 students (44.44%). Cycle II shows that there are 27 students who have the ability to formulate problems (75%), the ability to find information from various sources is achieved by 26 students (72.22%), 36 students have the ability to record the results of discussions (100%), while the ability to communicate is achieved by 25 students (100%). Based on the comparison of the results of the first and second cycle indicators, it illustrates that learning using the Two Stay Two Tray learning model with Windaw Shopping activities has been going well and can increase students' critical thinking potential. Recommendations from researchers for the use of the Two Stay Two Tray learning model with Windaw Shopping activities are (1) informing the learning activity model used to students early, so that students can follow the steps of this model correctly, (2) giving students the opportunity students look for enrichment materials in discussion activities (3) the teacher should have provided web-link directions that students can refer to in finding sources of information on the internet so that the source is valid or reliable (4) the formation of groups is sought to pay attention to the equitable distribution of students' abilities. ABSTRAK Penelitian ini bertujuan meningkatkan potensi berpikir kritis dalam pembelajaran sejarah dengan menggunakan model pembelajaran Two Stay Two Tray dengan aktivitas Windaw Shopping pada peserta didik XI MIPA 2 di SMA negeri 10 Malang. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, setiap siklus dilaksanakan dalam 5 tahap yaitu perencanan, pelaksanaan, pengamatan, evaluasi dan refleksi. Kelas XI MIPA2 SMA Negeri 10 Malang Semester genap Tahun Pelajaran 2018/2019 berjumlah 36 peserta didik. Hasil penelitian menunjukan bahwa pada siklus I hanya ada 15 peserta didik yang memiliki kemampuan merumuskan masalah (41,66%), kemampuan mencari informasi dari berbagai sumber dicapai oleh 15 peserta didik (41,66%) ,18 peserta didik memiliki kemampuan merekam hasil diskusi (50%), sedangkan kemampuan mengomunikasikan dicapai oleh 16 peserta didik (44,44%). Siklus II menunjukan bahwa ada 27 peserta didik yang memiliki kemampuan merumuskan masalah (75%), kemampuan mencari informasi dari berbagai sumber dicapai oleh 26 peserta didik ( 72,22%), 36 peserta didik memiliki kemampuan merekam hasil diskusi (100%), sedangkan kemampuan mengomunikasikan dicapai oleh 25 Peserta didik (100%). Berdasarkan perbandingan hasil capaian indikator siklus kesatu dan kedua menggambarkan bahwa pembelajaran dengan menggunakan model pembelajaran Two Stay Two Tray dengan aktivitas Windaw Shopping telah berlangsung dengan baik dan dapat meningkatkan potensi berpikir kritis peserta didik. Rekomendasi dari peneliti untuk penggunaan model pembelajaran Two Stay Two Tray dengan aktivitas Windaw Shopping adalah (1) menginformasikan model kegiatan pembelajaran yang digunakan pada peserta didik lebih awal, agar peserta didik dapat mengikuti langkah-langkah model ini dengan benar, (2) memberi kesempatan peserta didik mencari bahan pengayaan dalam kegiatan diskusi (3) sebaiknya guru sudah memberi arahan link- web yang bisa di rujuk peserta didik dalam mecari sumber informasi di internet agar sumbernya valid atau dapat dipercaya (4) pembentukan kelompok diupayakan memperhatikan pemerataan kemampuan peserta didik.